Taste disorders are partly genetically determined: Role of the TAS2R38 gene, a pilot study. (23rd January 2019) - Melis, Melania; Grzeschuchna, Lisa; Sollai, Giorgia; Hummel, Thomas; Tomassini Barbarossa, Iole
Abstract : Objectives/Hypothesis: Taste sensitivity varies greatly among individuals influencing eating behavior and health, consequently the disorders of this sense can affect the quality of life. The ability to perceive the bitter of thiourea compounds, such as phenylthiocarbamide (PTC), has been largely reported as a marker of the general taste sensitivity, food preferences, and health. PTC sensitivity is mediated by the TAS2R38 receptor and its genetic common variants. We study the role of the TAS2R38 receptor in taste disorders with the aim of understanding if these can be genetically determined. Study Design: Prospective cohort study. Methods: Differences in the PTC responsiveness between the patients cohort and healthy controls were assessed. All subjects received standardized tests for smell and taste function and were genotyped for the TAS2R38 gene. Results: PAV/PAV homozygous patients gave high PTC ratings, whereas PAV/AVI genotypes reported lower values, which are similar to those determined in AVI/AVI or rare genotypes. In addition, the patients cohort did not meet the Hardy‐Weinberg equilibrium at the TAS2R38 locus, showing a very low frequency of subjects carrying the PAV/AVI diplotype. Independently, in healthy controls who were in equilibrium at the locus, PAV/PAV homozygous and heterozygous rated PTC bitterness higher compared to AVI/AVI or rare genotypes. Conclusions: Our findings, by showing that an only taster haplotype (PAV) is not sufficient to evoke high responses of TAS2R38 receptor in patients with taste disorders, suggest that the genetic constitution may represent a risk factor for the development of taste disorders. Level of Evidence: 2c Laryngoscope, 129:E307–E312, 2019